Identification, characterization and expression analysis of transient receptor potential channel genes in the oriental fruit fly, Bactrocera dorsalis - Hong-ai Su; Xue Bai; Tian Zeng; Yong-yue Lu; Yi-xiang Qi (BMC Genomics, 2018)
Abstract Background Members of the transient receptor potential (TRP) superfamily are proteins that are critical for insects to detect changes in environmental stimuli and also play key roles in their sensory physiology. Moreover, this family provides potential targets for the design of insecticides. In contrast to a large number of studies conducted on Drosophila melanogaster, molecular studies to characterize TRP channels in agricultural pests are lacking. Results In this study, we identified 15 TRP channel genes in the genome of a notorious agricultural pest, the oriental fruit fly (Bactrocera dorsalis). Comparative analysis of the TRP channels (TRPs) in B. dorsalis with those in D. melanogaster, Glossina morsitans, Musca domestica and the closely related Ceratitis capitata, and TRPs from mosquitoes, Hymenoptera, Lepidoptera, Coleoptera and Hemiptera reveals that members of TRPA and TRPP subfamily are most diverse among insects. The results also suggest that Tephritidae family have two TRP-Polycystin 2 members even though most insects either possess just one or none. The highest expression levels of these two genes are in the testes of B. dorsalis, implying a role in regulating sperm function. We analyzed the expression profiles of the TRP channels identified in this study at different life stages using quantitative real time PCR. The results of this study demonstrate that all TRP channels are mainly expressed in adults, especially at mature stages. The one exception to this trend is BdTRPM, which is more highly expressed in the eggs of B. dorsalis, implying an important role in early development. We also detected the spatial expression of TRP channels in mature adult fruit flies by investigating expression levels within various tissues including those involved in sensory function, such as antennae, compound eyes, mouthparts, legs, and wings, as well as tissues critical for homeostasis and physiology (i.e., Malpighian tubules, the brain and gut as well as fat bodies, ovaries, and testes). Conclusion The results of this study establish a solid foundation for future functional characterization of B. dorsalis TRP channels as well as those of other insects and will help future insecticide design targeting these channels.